Battery separator and preparation method thereof, and secondary battery
By using viscous microspheres embedded in ceramic coating in lithium battery separators, the problem of difficulty in taking into account the breathability, wet bonding strength, heat resistance and internal resistance of existing separators is solved, and higher battery safety and service life are achieved.
Patent Information
- Application Number
- CN202411997167.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
While improving breathability, wet bonding strength and heat resistance, existing lithium battery separators are difficult to take into account low internal resistance and low powder drop rate, resulting in insufficient comprehensive performance of the battery.
A ceramic coating containing viscous microspheres is used. The sum of the surface areas of the viscous microspheres embedded in the ceramic coating accounts for 50% to 98% of the total surface areas. The viscous microspheres embedded in the ceramic coating during the drying process through a high-frequency vibration roller to ensure sufficient contact and improve the performance of the membrane.
The battery separator has high breathability and wet bonding strength, and has low internal resistance, low powder drop rate and high heat resistance, which improves the safety, circulation efficiency and service life of the battery.
Smart Images

Figure CN119786885A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of secondary battery separators, and in particular relates to a battery separator and a preparation method thereof, and a secondary battery. Background Art
[0002] As the concept of environmental protection has gained popularity, the market share of new energy industries represented by lithium-ion batteries has been increasing. The current market has higher and higher requirements for the endurance of lithium batteries, which has led to the continuous increase in the energy density of lithium batteries. However, the result is that the internal components of lithium batteries need to have lower internal resistance and stronger heat resistance, so as to improve the overall performance of lithium batteries.
[0003] As one of the key components of lithium batteries, the diaphragm is responsible for isolating the positive and negative electrodes, preventing battery short circuits, and providing a transmission channel for lithium ions. Currently, most common diaphragms use ceramics and polymers as coatings to reduce the internal resistance of the battery, improve the adhesion between the electrode and the diaphragm, and the heat resistance of the diaphragm. At the same time, it can block some reducing gases generated by overheating of the battery's negative electrode, but the improvement effect of the above performance is not significant.
[0004] How to obtain a diaphragm that takes into account all of the above properties remains a problem that needs to be solved urgently in this field. Summary of the invention
[0005] The object of the present invention is to provide a battery separator, which has good air permeability, good wet bonding strength, good air permeability, low powder loss rate and low internal resistance.
[0006] The present invention also aims to provide a method for preparing a battery separator.
[0007] Another object of the present invention is to provide a secondary battery.
[0008] In the first aspect, the present invention provides a battery separator, comprising a base film and a coating coated on at least one surface of the base film, wherein the coating is a ceramic coating containing sticky microspheres, the sticky microspheres are embedded in the ceramic coating, and the sum of the surface areas of the sticky microspheres embedded in the ceramic coating accounts for 50% to 98% of the total surface area of the sticky microspheres.
[0009] In a second aspect, the present invention provides a method for preparing the battery separator, comprising the following steps:
[0010] The ceramic particles are mixed with water, dispersed to form an inorganic dispersion, and the viscous microsphere solution is added and dispersed evenly to obtain a finished slurry;
[0011] The finished slurry is coated on at least one side of the base film, and then dried in a three-stage oven, the first stage drying pressure is -40 to -10Pa, the drying temperature is 65 to 80°C, the second stage drying pressure is -80 to -40Pa, the drying temperature is 65 to 90°C, the third stage drying pressure is -80 to -60Pa, the drying temperature is 65 to 70°C, the roller at the 1 / 2 to 2 / 3 position after the first roller is set as a high-frequency vibration roller, the frequency of the high-frequency vibration roller is 20 to 40khz, and the diaphragm is obtained after drying.
[0012] In a third aspect, the present invention provides a secondary battery comprising the battery separator described above.
[0013] Beneficial effects of the present invention:
[0014] The battery separator provided by the present invention has a surface area of the sticky microspheres embedded in the ceramic coating portion that accounts for 50% to 98% of the total surface area of the sticky microspheres, which can ensure sufficient contact between the sticky microspheres and the inorganic particles in the ceramic coating, and can ensure that the separator has good air permeability while also having good wet bonding strength, good air permeability, low powder loss rate, and low internal resistance, so that the battery containing the separator has higher safety, higher battery cycle efficiency, and stronger heat resistance, further extending the service life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 This is a schematic diagram of the structure of the high-liquid-retention coated battery separator of the present invention;
[0016] Wherein, R1 represents the diameter of the polymer microsphere, a represents the polymer microsphere, b represents the ceramic particles, and c represents the base film.
[0017] Figure 2 It is a schematic diagram of the structure of the viscous microspheres embedded in the ceramic coating in the high-liquid-retention coated battery separator of the present invention.
[0018] Wherein, R represents the radius of the polymer microsphere, a represents the polymer microsphere, c represents the base film, d represents the interface, △h represents the height of the polymer microsphere protruding from the upper surface, h represents the embedding depth of the polymer microsphere, and H represents the coating thickness. DETAILED DESCRIPTION
[0019] The present invention is described in detail below by way of examples. It is necessary to point out that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Those skilled in the art in this field can make some non-essential improvements and adjustments to the present invention based on the above content of the present invention.
[0020] The present invention provides a high-liquid-retention coated battery separator, comprising a base film and a coating coated on at least one surface of the base film, wherein the coating is a ceramic coating comprising a plurality of sticky microspheres, wherein the plurality of sticky microspheres are embedded in the ceramic coating, and the sum of the surface areas of the plurality of sticky microspheres embedded in the ceramic coating accounts for 50% to 98% of the total surface area of the plurality of sticky microspheres, specifically 50%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 98%, preferably 70% to 98%.
[0021] The contact surface of each sticky microsphere inside the ceramic coating is the interface between the ceramic coating and the sticky microsphere. The interface area is the surface area of the sticky microsphere in the coating. The existence of this interface will significantly enhance the adsorption effect of the battery separator on the electrolyte, improve the air permeability of the battery separator, affect the bonding ability between the separator and the electrode, improve the powder loss rate of the separator and ensure that the battery has a smaller internal resistance value.
[0022] The ratio of the sum of the surface areas of the adhesive microspheres embedded in the ceramic coating portion to the total surface area of the adhesive microspheres can be measured by the following method:
[0023] Ten 5 cm × 5 cm coated membrane samples were cut, of which five were cut vertically along the TD direction, and a Zeiss field emission scanning electron microscope (ZEISS SIGMA 300 at 500 times the field of view) was used to measure the sum of the surface areas of the microspheres protruding from the outer surface of the test coating n1 and the sum of the interfaces of the microspheres n2 within the scope of the microscope. Five of the 5 were cut vertically along the MD direction, and a Zeiss field emission scanning electron microscope (ZEISS SIGMA 300 at 500 times the field of view) was used to measure the sum of the surface areas of the microspheres protruding from the outer surface of the test coating n3 and the sum of the interfaces of the microspheres n4 within the scope of the microscope. Then, the ratio of the sum of the interface surface areas of the sticky microspheres to the total surface area is: The battery separator described in the present invention has the contact surface between the ceramic coating and the base film as the inner surface, and the other opposite surface as the outer surface. The vertical distance between the bottom of the sticky microsphere and the outer surface is the embedding depth h, and the thickness of the ceramic coating is H. For any of the sticky microspheres, h>1 / 2H should be satisfied, that is, the minimum embedding depth of all sticky microspheres is greater than 1 / 2H, such as h can be 2 / 3H, 3 / 4H, 4 / 5H, H.
[0024] The embedding depth h of the viscous microspheres of the battery separator of the present invention can be measured by the following method:
[0025] Cut 10 coated separator specimens with a size of 5 cm × 5 cm. Among them, 5 specimens are vertically cut along the TD direction, and the other 5 specimens are vertically cut along the MD direction. Using a Zeiss field emission scanning electron microscope (under a 500-fold electron microscope field of view, ZEISS SIGMA 300), measure the vertical distance from the bottom of the viscous microsphere to the outer surface of the coating within the field of view of the microscope as the embedding depth h.
[0026] In some embodiments of the present invention, for any one of the viscous microspheres, it should satisfy 1 / 2H < h < H. For example, h can be 0.55H, 0.6H, 0.65H, 0.7H or H, or a range value between any intermediate values thereof. In the present invention, the viscous microspheres are embedded in the ceramic coating. For any one of the viscous microspheres, satisfying h > H / 2 can ensure that the air permeability of the separator coating is within a suitable range, can balance a relatively small internal resistance and good high-temperature thermal stability, and has a low powder shedding rate and high separator safety, providing better battery cycle performance and longer service life for the battery. For any one of the viscous microspheres, a large embedding depth makes the separator have better air permeability, as well as a relatively small powder shedding rate and a relatively small compression rate. However, if the embedding depth is too large, it will affect the wet bonding strength of the separator; if the embedding depth is too shallow, the separator will have better thermal shrinkage and a relatively good internal resistance value, but if the embedding is too small, it will seriously affect the air permeability, wet bonding strength and powder shedding rate of the separator.
[0027] For the battery separator described in the present invention, taking the contact surface between the ceramic coating and the base film as the inner surface and the opposite side as the outer surface, 20% - 70% of the viscous microspheres protrude from the outer surface of the ceramic coating, and the remaining viscous microspheres are buried below the outer surface. For example, 20% of the viscous microspheres protrude from the outer surface and 80% are buried below the outer surface, or 30% of the viscous microspheres protrude from the outer surface and 70% are buried below the outer surface, or 40% of the viscous microspheres protrude from the outer surface and 60% are buried below the outer surface, or 50% of the viscous microspheres protrude from the outer surface and 50% are buried below the outer surface, or 60% of the viscous microspheres protrude from the outer surface and 40% are buried below the outer surface, or 70% of the viscous microspheres protrude from the outer surface and 30% are buried below the outer surface. In the present invention, "quantity" refers to the number of viscous microspheres. By dispersing a plurality of viscous microspheres in the ceramic coating of the separator, some of the viscous microspheres protrude from the outer surface of the ceramic coating, and the parts of the protruding viscous microspheres that leak outside the ceramic coating form channels with each other for storing electrolyte and allowing electrolyte to flow through; the viscous microspheres buried in the ceramic coating play a supporting role for the ceramic coating. The inventors found during the R & D process that by controlling 20% - 70% of the viscous microspheres in the battery separator to protrude from the outer surface of the ceramic coating, the battery separator can have good air permeability, thermal stability, adhesiveness and liquid absorption rate.
[0028] The percentage of sticky microspheres protruding from the outer surface of the ceramic coating is calculated by the following method:
[0029] Ten 5 cm × 5 cm coated diaphragm samples were cut, of which 5 were cut vertically along the TD direction. The ultra-depth-of-field microscope (under a 500x electron microscope field of view, Keyence, VHX-7000N) was used to observe the range of the microscope. The number of sticky microspheres was recorded as n1, the number of sticky microspheres protruding from the outer surface of the ceramic coating was recorded as n2, and the proportion of sticky microspheres protruding from the outer surface of the ceramic coating in the TD direction was n. TD =n2 / n1, repeat the test for 5 groups of samples and take the average value; another 5 samples were cut vertically along the MD direction and observed using an ultra-depth microscope (under a 500x electron microscope field of view, Keyence, VHX-7000N) within the viewing range. The number of sticky microspheres was recorded as n3, the number of sticky microspheres protruding from the outer surface of the ceramic coating was recorded as n4, and the proportion of sticky microspheres protruding from the outer surface of the ceramic coating in the MD direction was n. MD = n4 / n3, repeat the test for 5 groups of samples and take the average value, then the proportion of microspheres protruding from the outer surface of the ceramic coating = (n TD +n MD ) / 2.
[0030] In the high-liquid retention coated battery separator of the present invention, preferably 50-60% of the adhesive microspheres protrude from the outer surface of the ceramic coating.
[0031] The battery separator described in the present invention, the ceramic particles in the ceramic coating include one or more of α-alumina, γ-alumina, boehmite, calcium carbonate, barium sulfate, barium titanate, hydrotalcite, montmorillonite, spinel, titanium dioxide, silicon dioxide, zirconium dioxide, magnesium oxide, calcium oxide, beryllium oxide, magnesium hydroxide, calcium hydroxide, and silicon carbide, preferably boehmite.
[0032] The battery separator of the present invention has an average particle size D V50 It can be 0.05 to 1.5 μm, such as 0.05 μm, 0.1 μm, 0.5 μm, 0.7 μm, 0.9 μm, 1.0 μm, 1.2 μm, 1.5 μm, preferably 0.1 to 1.0 μm.
[0033] In the battery separator of the present invention, the thickness of the ceramic coating is 1-5 μm, such as 1 μm, 2 μm, 3 μm, 4 μm, or 5 μm.
[0034] The battery separator described in the present invention, the viscous microspheres include one or more of polyimide water-soluble microspheres, styrene-butadiene rubber microspheres, polyacrylate modified microspheres, polyetherimide, aramid, aromatic sulfone, polyvinylidene fluoride, polymethyl methacrylate, thermoplastic polyurethane elastomer rubber, polyethylene terephthalate, polyethylene oxide, polyacrylonitrile, polyvinylidene fluoride and polyvinylidene fluoride-hexafluoropropylene, preferably polymethyl methacrylate.
[0035] In the battery separator of the present invention, the glass transition temperature of the polymethyl methacrylate is 30 to 100° C., preferably 50 to 100° C., and more preferably 60 to 100° C. If the glass transition temperature is too low, the surface area of the ceramic coating portion where the sticky microspheres are embedded will be affected, thereby affecting the thermal shrinkage and adhesion of the separator, and further affecting the compression rate and powder loss rate of the separator.
[0036] The battery separator of the present invention is characterized in that the average particle size D of the sticky microspheres is V50 The diameter of the nanostructured carbon foam is 1 to 10 μm, such as 1 μm, 3 μm, 5 μm, 7 μm, or 10 μm, preferably 1 to 8 μm, and more preferably 1 to 6 μm.
[0037] The battery separator of the present invention, the base film is made of polyethylene and / or polypropylene, and the thickness of the base film is 5 to 15 μm, such as 5 μm, 7 μm, 10 μm, 13 μm, 15 μm.
[0038] In the battery separator of the present invention, the ceramic coating is coated on one or both surfaces of the base film.
[0039] In the battery separator of the present invention, the solid mass ratio of the ceramic particles to the sticky microspheres is (20-40):(1-3), such as 20:3, 20:2, 20:1, 25:1, 30:1, 30:2, 35:1, 40:1, preferably (25-35):(1-2).
[0040] The method for preparing the battery separator of the present invention comprises the following steps:
[0041] The ceramic particles are mixed with water and dispersed to form an inorganic dispersion, and then the viscous microsphere solution is added and dispersed evenly to obtain a finished slurry;
[0042] The finished slurry is coated on the base film and then dried in a three-stage oven. The first stage drying pressure is -40 to -10Pa, such as -40Pa, -30Pa, -20Pa, and -10Pa, and the drying temperature is 65 to 80°C, such as 65°C, 70°C, 75°C, and 80°C. The second stage drying pressure is -80 to -40Pa, such as -80Pa, -70Pa, -60Pa, -50Pa, and -40Pa, and the drying temperature is 65 to 90°C, such as 65°C, 70°C, 75°C, and 80°C. , 85℃, 90℃, the drying pressure of the third stage is -80~-60Pa, such as -80Pa, -70Pa, -60Pa, the drying temperature is 65~70℃, such as 65℃, 70℃, the roller at the position 1 / 2~2 / 3 (for example, 1 / 2 or 2 / 3) after the first roller is set as a high-frequency vibration roller, and the frequency of the high-frequency vibration roller is 20~40khz. In the oven, the length ratio of the first section: the second section: the third section is (2~3): 1: (2~3), and is further preferably 2: 1: 2. After the drying, the diaphragm is obtained.
[0043] The method of the present invention is dried in a three-stage drying manner, and the drying process is carried out under negative pressure conditions. At the same time, in the second half of the first drying process, the roller is set as a high-frequency vibration roller. When the diaphragm coating is wet, the high-frequency vibration is combined to accelerate the sedimentation of the viscous microspheres. At a certain vibration frequency, the total area of the viscous microspheres embedded in the ceramic coating meets the requirements of this application. At the same time, the frequency and number of high-frequency vibration rollers can be adjusted based on actual needs, and high-frequency vibration rollers can be selectively set in the front section of the second drying process to increase the area ratio of the viscous microspheres embedded in the ceramic coating.
[0044] In the method for preparing the battery separator of the present invention, the solid content of the viscous microsphere solution is 10-40wt%, such as 10wt%, 20wt%, 30wt%, 40wt%, preferably 20-35wt%, and more preferably 25-30wt%.
[0045] The preparation method of the battery separator described in the present invention, the solid content of the finished slurry is 30-40wt%, such as 30wt%, 32wt%, 33wt%, 34wt%, 35wt%, 36wt%, 37wt%, 38wt%, 40wt%, preferably 32-38wt%, the solid content of the finished slurry will directly affect the floating degree of the sticky microspheres, the higher the solid content, the smaller the floating, the lower the solid content, the higher the floating. The present invention uses a finished slurry with a solid content of 32-38%, so that the sticky microspheres are solidified inside the coating to avoid floating and sinking.
[0046] The preparation method of the battery separator described in the present invention, the finished slurry contains 0.1 to 30 parts by weight of sticky microspheres, such as 0.1 parts by weight, 5 parts by weight, 10 parts by weight, 15 parts by weight, 20 parts by weight, 25 parts by weight, 30 parts by weight, and 15 to 40 parts by weight of ceramic particles, such as 15 parts by weight, 20 parts by weight, 25 parts by weight, 30 parts by weight, 35 parts by weight, 40 parts by weight.
[0047] The preparation method of the battery separator of the present invention is to coat the finished slurry onto the base film using a coating machine, the depth of the gravure roll is 20 to 100 μm, such as 20 μm, 30 μm, 50 μm, 70 μm, 90 μm, 100 μm, preferably 20 to 50 μm; the coating speed is 50 to 250 m / min, such as 50 m / min, 100 m / min, 150 m / min, 200 m / min, 250 m / min. The deeper the gravure depth, the lower the position of the sticky microspheres in the coating. The structural stability separator of the present invention is coated with a gravure roll with a deeper depth while meeting the coating amount requirements.
[0048] The preparation method of the battery separator described in the present invention, the finished slurry also includes one or more of a binder, a wetting agent and a dispersant, the amount of the thickener is ≤15 parts by weight, the amount of the binder is ≤15 parts by weight, the amount of the wetting agent is ≤3 parts by weight, and the amount of the dispersant is ≤3 parts by weight; the thickener, binder, wetting agent and dispersant are all commonly used substances in the field, wherein the binder can be one or more of styrene-butadiene rubber, acrylate, polyvinyl alcohol, polyacrylonitrile, polyvinylidene fluoride, polyethylene oxide, polytetrafluoroethylene; the wetting agent can be one or more of anionic surfactants, polyethylene surfactants, polyol surfactants, for example, can be polyether-modified siloxane or alkylphenol polyoxyethylene ether; the dispersant can be one or more of polyvinyl pyrrolidone, polyacrylamide, polyvinyl alcohol, sodium polyacrylate.
[0049] A secondary battery comprises the battery separator mentioned above.
[0050] The present invention is described below by means of specific examples.
[0051] Examples 1 to 9
[0052] Boehmite and sodium polyacrylate (solid content 50%) are dispersed in water, and dispersed by sand mill (speed 1000rpm, 30mmin) to form a dispersion, polymethyl methacrylate is added, and after uniform dispersion, acrylate (solid content 45%), sodium polyacrylate, and alkylphenol polyoxyethylene ether (solid content 100%) are added in sequence, dispersed evenly, and sieved to form a finished slurry.
[0053] The finished slurry is coated on the base film by a coating machine, the depth of the gravure roller is 30 μm, the coating speed is 150 m / min, and the traction roller pulls the slurry into the oven for drying. The oven is divided into three sections. The roller at the half position after the first section is set as a high-frequency vibration roller with a frequency of 30 khz. The length ratio of the first section: the second section: the third section is 2 / 5: 1 / 5: 2 / 5.
[0054] The amount of each raw material used and the preparation process conditions in Examples 1 to 9 are shown in Table 1.
[0055] Comparative Example 1
[0056] The only difference from Example 1 is that the glass transition temperature and solid content of PMMA in the finished slurry are different.
[0057] Comparative Example 2
[0058] The only difference from Example 2 is that no high-frequency vibration roller is provided during the drying process.
[0059] The battery separators prepared in the examples and comparative examples were subjected to performance tests, and the test results are shown in Table 1.
[0060] The performance test method is:
[0061] Air permeability (s / (100cc)):
[0062] The test was conducted in accordance with the requirements of GB / T36363-2018. A 600mm×100mm membrane sample was cut and a Wangyan air permeability meter (ASAHI Co., Ltd., EG01-55-1MR) was used for a test time of 3s. The air permeability of the membrane was measured at any position with an interval of 100mm along the 600mm TD direction. The average value of the above five test points was recorded as the air permeability of the membrane.
[0063] Thermal shrinkage (%):
[0064] Test according to the requirements of GB / T36363-2018. Cut a sample of 10cm×10cm, mark the transverse TD and longitudinal MD on the sample, measure the transverse and longitudinal widths with a fully automatic image measuring projector (Kunshan Gaopin Precision Instrument Co., Ltd., GP-300C), clamp the sample between two sealed A4 papers, place the sample in a 150℃ oven for 1h, and measure the transverse and longitudinal widths with a fully automatic image measuring projector after the sample returns to room temperature. Measure 3 times and take the average value:
[0065] MD heat shrinkage rate (%) = (MD length before heating - MD length after heating) ÷ MD length before heating × 100;
[0066] TD heat shrinkage rate (%) = (TD length before heating - TD length after heating) / TD length before heating × 100.
[0067] Wet bond strength (MPa.S):
[0068] Cut samples of 20mm*60mm size, pole pieces of 20mm*60mm size and PET of 20mm*60mm size, stack them according to diaphragm / pole piece / PET, put them into 80mm*80mm aluminum-plastic bag, inject 1.5g electrolyte (LiPF6 1M, EC:EMC=3 / 7, VC=2%), seal the edges with vacuum (-80kPa), and ripen for 24h; pad the top and bottom of the sample with silicone pads, use a hot press (Qmesys, QM940AS) for 10min, where the upper and lower clamps of the hot press are at 60℃ and the pressure is 200kgf, cool, take the sample out of the aluminum-plastic bag, manually peel off the PET, clamp the electrode in the lower chuck of a tensile testing machine (Jinan Sike Testing Technology Co., Ltd., TSL-1002), clamp the diaphragm in the upper chuck of the tensile testing machine, ensure that there is no tilt, the stretching speed is 300mm / min, measure three times, and take the average value.
[0069] Powder loss rate:
[0070] The battery diaphragm was cut into 6 pieces, 3cm×22cm in size, and placed on an analytical balance for weighing, and the weight was recorded as m1; ensure that the curved table of the friction color fastness tester (Daei Science Seiki Manufacturing Co., Ltd., RT-300S) is clean, and fix the lens paper on the friction head of the friction color fastness tester, where the smooth side of the lens paper faces outward, and then fix the cut battery diaphragm on the curved table of the friction color fastness tester, with one side of the heat-resistant coating facing up, and then gently place the friction head on the diaphragm after clamping, set the number of experiments to 5 on the operation panel of the color fastness tester, and click to start. After the experiment is completed, take out the battery diaphragm, place it on an analytical balance for weighing, and record the weight as m2. The powder loss amount M (mg) = m1-m2, and take the average value of the six groups of diaphragm test data. If the diaphragm is a double-layer coating on both sides of the base film, the weight of both sides of the diaphragm after friction testing is m2, and the powder loss data is calculated based on this.
[0071] Compression ratio:
[0072] The sample film was cut into 50*50mm square samples, and 5 cut samples were stacked together and measured with a Mahr thickness gauge (Mahr model: C1202) for 10 points of thickness, and the average value was recorded as D0; then the PET sheet was cut into 50*50mm square sheets, and the sample film was placed between two cut PET sheets and aligned, and placed in a hot press (Qmesys, QM940AS) for hot pressing; the hot pressing parameters were set to 1000kgf, 70℃, and the holding time was 1s. After taking out, the diaphragm after hot pressing was measured at 10 points, and the average value was recorded as D1. The compression rate
[0073] Internal resistance(Ω):
[0074] Cut a sample of 100mm×100mm size, ensure that there is no foreign matter on the surface of the insulation resistance test bench, place the sample in the specified area of the test bench, start the YD9820A program-controlled insulation resistance tester (Changzhou Yangzi Electronics Co., Ltd.) for testing, with a voltage of 100V, a time of 5s, and a pressure of 0.05MPa. Test 5 groups and take the average value.
[0075] Table 1
[0076]
[0077]
[0078] It can be seen from Examples 1 to 9 that when the sum of the surface areas of the sticky microspheres embedded in the ceramic coating accounts for 50% to 98% of the total surface area of the sticky microspheres, the battery separator has good air permeability, thermal stability, wet adhesion strength, powder loss rate, compression rate and small internal resistance, while in Comparative Example 1, since the sum of the surface areas of the sticky microspheres embedded in the ceramic coating accounts for too large a proportion of the total surface area of the sticky microspheres, the separator has poor air permeability, wet adhesion strength and compression rate; in Comparative Example 2, since the sum of the surface areas of the sticky microspheres embedded in the ceramic coating accounts for too small a proportion of the total surface area of the sticky microspheres, the separator has poor air permeability, thermal stability, powder loss rate and internal resistance.
[0079] Of course, the present invention may have many other embodiments. Without departing from the spirit and essence of the present invention, technicians familiar with the field may make various corresponding changes and deformations based on the present invention, but these corresponding changes and deformations should all fall within the scope of protection of the claims of the present invention.
Claims
1. A battery separator, comprising a base film and a coating coated on at least one surface of the base film, wherein the coating is a ceramic coating containing adhesive microspheres, characterized in that: The sticky microspheres are embedded in the ceramic coating, and the sum of the surface areas of the parts of the sticky microspheres embedded in the ceramic coating accounts for 50% to 98% of the total surface area of the sticky microspheres.
2. The battery separator according to claim 1, characterized in that: The contact surface between the ceramic coating and the base film is the inner surface, the other opposite surface is the outer surface, the vertical distance between the bottom of the sticky microsphere and the outer surface is the embedding depth h, the thickness of the ceramic coating is H, and for any of the sticky microspheres, h>1 / 2H should be satisfied.
3. The battery separator according to claim 2, characterized in that: The sum of the surface areas of the viscous microspheres embedded in the ceramic coating accounts for 70% to 98% of the total surface area of the viscous microspheres; for any of the viscous microspheres, 1 / 2H<h<H should be satisfied.
4. The battery separator according to claim 1, characterized in that: 20 to 70% of the adhesive microspheres protrude from the outer surface of the ceramic coating.
5. The battery separator according to claim 1, characterized in that: The ceramic particles in the ceramic coating include one or more of α-alumina, γ-alumina, boehmite, calcium carbonate, barium sulfate, barium titanate, hydrotalcite, montmorillonite, spinel, titanium dioxide, silicon dioxide, zirconium dioxide, magnesium oxide, calcium oxide, beryllium oxide, magnesium hydroxide, calcium hydroxide, and silicon carbide, preferably boehmite; The average particle size D of the ceramic particles v50 0.05 to 1.5 μm, preferably 0.1 to 1.0 μm; The thickness of the ceramic coating is 1-5 μm.
6. The battery separator according to claim 1, characterized in that: The sticky microspheres include one or more of polyimide water-soluble microspheres, styrene-butadiene rubber microspheres, polyacrylate-modified microspheres, polyetherimide, aramid, aramid fiber, polyvinylidene fluoride, polymethyl methacrylate, thermoplastic polyurethane elastomer rubber, polyethylene terephthalate, polyethylene oxide, polyacrylonitrile, polyvinylidene fluoride and polyvinylidene fluoride-hexafluoropropylene, preferably polymethyl methacrylate; The glass transition temperature of the polymethyl methacrylate is 30 to 100° C., preferably 50 to 100° C., and more preferably 60 to 100° C.; Optionally, the average particle size D of the sticky microspheres v50 It is 1 to 10 μm, preferably 1 to 8 μm, and more preferably 1 to 6 μm.
7. The battery separator according to claim 1, characterized in that: The base film is made of polyethylene and / or polypropylene, and has a thickness of 5 to 15 μm.
8. The battery separator according to any one of claims 1 to 7, characterized in that: The ceramic coating is coated on one or both surfaces of the base film.
9. The battery separator according to any one of claims 1 to 7, characterized in that: The solid mass ratio of the ceramic particles to the sticky microspheres is (20-40):(1-3), preferably (25-35):(1-2).
10. The method for preparing a battery separator according to any one of claims 1 to 9, characterized in that: The following steps are involved: The ceramic particles are mixed with water, dispersed to form an inorganic dispersion, and the viscous microsphere solution is added and dispersed evenly to obtain a finished slurry; The finished slurry is coated on at least one side of the base film, and then dried in a three-stage oven, the first stage drying pressure is -40 to -10Pa, the drying temperature is 65 to 80°C, the second stage drying pressure is -80 to -40Pa, the drying temperature is 65 to 90°C, the third stage drying pressure is -80 to -60Pa, the drying temperature is 65 to 70°C, the roller at the 1 / 2 to 2 / 3 position after the first stage roller is set as a high-frequency vibration roller, the high-frequency vibration roller frequency is 20 to 40khz, and the diaphragm is obtained after drying; In the oven, the length ratio of the first section: the second section: the third section is (2-3): 1: (2-3), preferably 2: 1: 2; the solid content of the viscous microsphere solution is 10-40wt%, preferably 20-35wt%, and more preferably 25-30wt%; The solid content of the finished slurry is 30-40wt%, preferably 32-38wt%; The finished slurry contains 0.1 to 30 parts by weight of sticky microspheres and 15 to 40 parts by weight of ceramic particles; The finished slurry is coated on the base film by a coating machine, the depth of the gravure roll is 20-100 μm, preferably 20-50 μm; the coating speed is 50-250 m / min, preferably 100-150 m / min.
11. The method for preparing a high-liquid retention coated battery separator according to claim 10, characterized in that: The finished slurry also includes one or more of a binder, a wetting agent and a dispersant.
12. A secondary battery, characterized in that: A battery separator comprising the battery separator according to any one of claims 1 to 9 or a battery separator prepared by the method according to any one of claims 10 to 11.
Citation Information
Cited By
A diaphragm, a diaphragm preparation method, a diaphragm coating slurry and a lithium battery
CN122638710A